Design, user experience, and usability. design discourse : 4th International Conference, DUXU 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: design discourse : 4th International Conference, DUXU 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Design discourse : Part I, (2015) - Unknown
No abstract available